Answer:
Gravity and magnetism are not the same thing. In fact, they are completely separate forces. Gravity is a force that acts between any two objects with mass. ... Magnetism can either pull the two objects together or push them apart, depending on which way the magnets point.
Explanation:
Answer:
-30 N/C
Explanation:
Since the potential changes from 0.90 V to 1.2 V when I move the probe 1 cm closer to the non-grounded electrode, the electric field is the gradient between the two points is given by E = -ΔV/Δx where ΔV = change in electric potential and Δx = distance of potential change = 1 cm = 0.01 m
Now ΔV = final potential - initial potential = 1.2 V - 0.90 V = 0.30 V
Since E = -ΔV/Δx
substituting the values of the variables into the equation, we have
E = -ΔV/Δx
E = -0.30 V/0.01 m
E = -30 V/m
Since 1 V/m = 1 N/C.
E = -30 N/C
So, the average electric field is -30 N/C
Answer:
4
Explanation:
G = Gravitational constant = 6.67 × 10⁻¹¹ m³/kgs²
= Mass of Earth
= Mass of Moon
r = Distance between Earth and Moon
Old gravitational force
![F_o=\dfrac{Gm_1m_2}{r^2}](https://tex.z-dn.net/?f=F_o%3D%5Cdfrac%7BGm_1m_2%7D%7Br%5E2%7D)
New gravitational force
![F_n=\dfrac{Gm_1m_2}{(\dfrac{1}{2}r)^2}](https://tex.z-dn.net/?f=F_n%3D%5Cdfrac%7BGm_1m_2%7D%7B%28%5Cdfrac%7B1%7D%7B2%7Dr%29%5E2%7D)
Dividing the equations
![\dfrac{F_n}{F_o}=\dfrac{\dfrac{Gm_1m_2}{(\dfrac{1}{2}r)^2}}{\dfrac{Gm_1m_2}{r^2}}\\\Rightarrow \dfrac{F_n}{F_o}=\dfrac{\dfrac{Gm_1m_2}{\dfrac{1}{4}r^2}}{\dfrac{Gm_1m_2}{r^2}}\\\Rightarrow \dfrac{F_n}{F_o}=4](https://tex.z-dn.net/?f=%5Cdfrac%7BF_n%7D%7BF_o%7D%3D%5Cdfrac%7B%5Cdfrac%7BGm_1m_2%7D%7B%28%5Cdfrac%7B1%7D%7B2%7Dr%29%5E2%7D%7D%7B%5Cdfrac%7BGm_1m_2%7D%7Br%5E2%7D%7D%5C%5C%5CRightarrow%20%5Cdfrac%7BF_n%7D%7BF_o%7D%3D%5Cdfrac%7B%5Cdfrac%7BGm_1m_2%7D%7B%5Cdfrac%7B1%7D%7B4%7Dr%5E2%7D%7D%7B%5Cdfrac%7BGm_1m_2%7D%7Br%5E2%7D%7D%5C%5C%5CRightarrow%20%5Cdfrac%7BF_n%7D%7BF_o%7D%3D4)
The ratio is ![\dfrac{F_n}{F_o}=4](https://tex.z-dn.net/?f=%5Cdfrac%7BF_n%7D%7BF_o%7D%3D4)
The new force would be 4 times the old force
Answer:
As an object’s temperature increases, the Rate at which it radiates energy increases.
Answer:
a) (0, -33, 12)
b) area of the triangle : 17.55 units of area
Explanation:
<h2>
a) </h2>
We know that the cross product of linearly independent vectors
and
gives us a nonzero, orthogonal to both, vector. So, if we can find two linearly independent vectors on the plane through the points P, Q, and R, we can use the cross product to obtain the answer to point a.
Luckily for us, we know that vectors
and
are living in the plane through the points P, Q, and R, and are linearly independent.
We know that they are linearly independent, cause to have one, and only one, plane through points P Q and R, this points must be linearly independent (as the dimension of a plane subspace is 3).
If they weren't linearly independent, we will obtain vector zero as the result of the cross product.
So, for our problem:
![\vec{A} = \vec{P} - \vec{Q} \\\\\vec{A} = (1,0,1) - (-2,1,4)\\\\\vec{A} = (1 +2,0-1,1-4)\\\\\vec{A} = (3,-1,-3)](https://tex.z-dn.net/?f=%5Cvec%7BA%7D%20%3D%20%5Cvec%7BP%7D%20-%20%5Cvec%7BQ%7D%20%5C%5C%5C%5C%5Cvec%7BA%7D%20%3D%20%281%2C0%2C1%29%20-%20%28-2%2C1%2C4%29%5C%5C%5C%5C%5Cvec%7BA%7D%20%3D%20%281%20%2B2%2C0-1%2C1-4%29%5C%5C%5C%5C%5Cvec%7BA%7D%20%3D%20%283%2C-1%2C-3%29)
![\vec{B} = \vec{R} - \vec{Q} \\\\\vec{B} = (6,2,7) - (-2,1,4)\\\\\vec{B} = (6 +2,2-1,7-4)\\\\\vec{B} = (8,1,3)](https://tex.z-dn.net/?f=%5Cvec%7BB%7D%20%3D%20%5Cvec%7BR%7D%20-%20%5Cvec%7BQ%7D%20%5C%5C%5C%5C%5Cvec%7BB%7D%20%3D%20%286%2C2%2C7%29%20-%20%28-2%2C1%2C4%29%5C%5C%5C%5C%5Cvec%7BB%7D%20%3D%20%286%20%2B2%2C2-1%2C7-4%29%5C%5C%5C%5C%5Cvec%7BB%7D%20%3D%20%288%2C1%2C3%29)
![\vec{A} \times \vec{B} = (A_y B_z - B_y A_z) \ \hat{i} - ( A_x B_z-B_xA_z) \ \hat{j} + (A_x B_y - B_x A_y ) \ \hat{k}](https://tex.z-dn.net/?f=%5Cvec%7BA%7D%20%5Ctimes%20%20%5Cvec%7BB%7D%20%3D%20%28A_y%20B_z%20-%20B_y%20A_z%29%20%5C%20%20%5Chat%7Bi%7D%20-%20%28%20A_x%20B_z-B_xA_z%29%20%5C%20%5Chat%7Bj%7D%20%2B%20%28A_x%20B_y%20-%20B_x%20A_y%20%29%20%5C%20%5Chat%7Bk%7D)
![\vec{A} \times \vec{B} = ( (-1) * 3 - 1 * (-3) ) \ \hat{i} - ( 3 * 3 - 8 * (-3)) \ \hat{j} + (3 * 1 - 8 * (-1) ) \ \hat{k}](https://tex.z-dn.net/?f=%5Cvec%7BA%7D%20%5Ctimes%20%20%5Cvec%7BB%7D%20%3D%20%28%20%28-1%29%20%2A%203%20-%201%20%2A%20%28-3%29%20%29%20%5C%20%20%5Chat%7Bi%7D%20-%20%28%203%20%2A%203%20-%208%20%2A%20%28-3%29%29%20%5C%20%5Chat%7Bj%7D%20%2B%20%283%20%2A%201%20-%208%20%2A%20%28-1%29%20%29%20%5C%20%5Chat%7Bk%7D)
![\vec{A} \times \vec{B} = ( - 3 + 3 ) \ \hat{i} - ( 9 + 24 ) \ \hat{j} + (3 + 8 ) \ \hat{k}](https://tex.z-dn.net/?f=%5Cvec%7BA%7D%20%5Ctimes%20%20%5Cvec%7BB%7D%20%3D%20%28%20-%203%20%2B%203%20%29%20%5C%20%20%5Chat%7Bi%7D%20-%20%28%209%20%2B%2024%20%29%20%5C%20%5Chat%7Bj%7D%20%2B%20%283%20%2B%208%20%29%20%5C%20%5Chat%7Bk%7D)
![\vec{A} \times \vec{B} = 0 \ \hat{i} - 33 \ \hat{j} + 12 \ \hat{k}](https://tex.z-dn.net/?f=%5Cvec%7BA%7D%20%5Ctimes%20%20%5Cvec%7BB%7D%20%3D%200%20%5C%20%20%5Chat%7Bi%7D%20-%2033%20%5C%20%5Chat%7Bj%7D%20%2B%2012%20%5C%20%5Chat%7Bk%7D)
![\vec{A} \times \vec{B} =(0, -33, 12)](https://tex.z-dn.net/?f=%5Cvec%7BA%7D%20%5Ctimes%20%20%5Cvec%7BB%7D%20%3D%280%2C%20-33%2C%2012%29)
<h2>B)</h2>
We know that
and
are two sides of the triangle, and we also know that we can use the magnitude of the cross product to find the area of the triangle:
![|\vec{A} \times \vec{B} | = 2 * area_{triangle}](https://tex.z-dn.net/?f=%20%7C%5Cvec%7BA%7D%20%5Ctimes%20%20%5Cvec%7BB%7D%20%7C%20%3D%202%20%2A%20area_%7Btriangle%7D)
so:
![\sqrt{(-33)^2 + (12)^2} = 2 * area_{triangle}](https://tex.z-dn.net/?f=%20%5Csqrt%7B%28-33%29%5E2%20%2B%20%2812%29%5E2%7D%20%3D%202%20%2A%20area_%7Btriangle%7D)
![\sqrt{1233} = 2 * area_{triangle}](https://tex.z-dn.net/?f=%20%5Csqrt%7B1233%7D%20%3D%202%20%2A%20area_%7Btriangle%7D)
![35.114= 2 * area_{triangle}](https://tex.z-dn.net/?f=%2035.114%3D%202%20%2A%20area_%7Btriangle%7D)
![17.55 \ units \ of \ area = area_{triangle}](https://tex.z-dn.net/?f=%2017.55%20%5C%20units%20%5C%20%20of%20%5C%20area%20%3D%20%20area_%7Btriangle%7D)